Automatic Data Extraction And Management Through Integration With Database At RPT Lab Infineon Technologies - Hamdan, Mohd Syamil (2020)
Due to increase in demand and request for reliability qualification and evaluation, Reliability Product Testing (RPT) Lab in Infineon Technologies also outsource electrical testing process at available production testers at production block. However, electrical testing cannot be done through Reliability Evaluation and Logistic Information System (REALIS), instead, it has to be done offline. Due to this certain limitation and condition, data log is sometimes unable to be generated by testers, hence effort and time of operator or technician who conduct the electrical test is wasted. Bound with critical timeline to meet customer demand, missing data log is a huge loss in effort, energy, time and cost for RPT. The main objectives of this research is to identify root cause of data log not able to be produced when test is completed. Apart from that, this study is to optimize existing workflow in preparing the data logs that comply with RPT standard format and are readable by customers. Last but not least, aim of this research is to evaluate the overall benefit of the proposed system. Ishikawa fishbone diagram, flow chart, time study and survey are used to execute the objectives. After the implementation of new flow system, the average rate of missing data log has been significantly reduced and eliminated. The lead time of preparing the data log process has been tremendously reduced to half, from 83.5 minutes/lot to 44.9 minutes/lot. The number of software and application used are also reduced from six to two. Positive feedback from operation team on user-friendliness, efficiency and ergonomic topic have been highlighted and discovered.